Social representation: A theoretical review of the approach (Research, Society and Development, 2021)
This article aims to present the Theory of Social Representations, created by Serge Moscovici in 1961, as well as the contributions that several authors have created from it. This study makes a bibliographic review through scientific articles and books of several scholars who seek to understand and explain this approach of the daily practice of the human being, which is a reading of reality constituted through the thoughts of individuals from a particular group, which together produce a central core, where their ideas, thoughts, understanding about a particular object or phenomenon are translated. Social representation as an approach has great importance in studies that seek to understand social phenomena in order to create appropriate mechanisms to meet the needs of a given group. This article also brings the historical and epistemological contextualization of the theory, the processes of objectification and anchoring, the function of social representations and the forms of knowledge being consensual and reified and beyond its theoretical approaches: cultural, structural and societal.